Defects improved photocatalytic ability of TiO2 - Li, Lei (2014)
Defect generation forms an important means modulating the photocatalytic ability of TiO2 with mechanisms that remain yet unclear. Here we show that a spectral distillation clarifies the impact of defect on modulating the band gap, electroaffinity, and work function of the substance. Firstly, by analyzing XPS measurements, we calibrated the 2p3/2 level of 451.47 eV for an isolated Ti atom and its shifts by 2.14 and 6.94 eV, respectively, upon Ti and TiO2 bulk formation. Spectral difference between the defected and the un-defected TiO2 skin revealed then that the 2p3/2 level shifts further from 6.94 to 9.67 eV due to the defect-induced quantum entrapment. This entrapment is associated with an elevation of the upper edges of both the 2p3/2 and the conduction band by polarization. The shortening and strengthening of bonds between undercoordinated atoms densify and entrap the core electrons, which in turn polarize the dangling bond electrons of defect atoms. The entrapment and polarization mediate thus the band gap, the electroaffinity, the work function, and the photocatalytic ability of TiO2.